2011
DOI: 10.1111/j.1537-2995.2011.03292.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytapheresis versus phlebotomy in the initial treatment of HFE hemochromatosis patients: results from a randomized trial

Abstract: Erythrocytapheresis is highly effective treatment to reduce iron overload and from a societal perspective might potentially also be a cost-saving therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 26 publications
6
84
1
1
Order By: Relevance
“…As each procedure can remove up to 800 ml of red blood cells, more iron can be removed than by standard phlebotomy [93]. Its efficiency was shown in a randomised trial comparing TE and phlebotomy in individuals with HFE-related HH where an average of nine TE treatments were required to normalise SF compared to 27 phlebotomies [102]. The frequency of TE treatment is every two to three weeks and thus is less frequent compared to twiceweekly phlebotomies.…”
Section: Erythrocytapheresismentioning
confidence: 98%
See 2 more Smart Citations
“…As each procedure can remove up to 800 ml of red blood cells, more iron can be removed than by standard phlebotomy [93]. Its efficiency was shown in a randomised trial comparing TE and phlebotomy in individuals with HFE-related HH where an average of nine TE treatments were required to normalise SF compared to 27 phlebotomies [102]. The frequency of TE treatment is every two to three weeks and thus is less frequent compared to twiceweekly phlebotomies.…”
Section: Erythrocytapheresismentioning
confidence: 98%
“…The frequency of TE treatment is every two to three weeks and thus is less frequent compared to twiceweekly phlebotomies. The other advantages of TE are an overall shorter duration of therapy to normalise SF [102,103], its feasibility in patients with hypoproteinaemia and cardiac failure and a lower rate of hypovolaemia related reactions [93]. TE can maintain a euvolaemic state even with a larger volume of red cells removed as volume can be replaced by saline.…”
Section: Erythrocytapheresismentioning
confidence: 99%
See 1 more Smart Citation
“…In the induction phase, however, phlebotomy and erythrocytapheresis are still the most effective treatments to reduce the iron overload. 9 Clinical observations in HH patients on maintenance phlebotomy treatment showed that those who took proton pump inhibitors (PPIs) during longer periods needed fewer phlebotomies to maintain their SF level at around 50 mg/L. The intriguing question of what is the mechanism of this reduction in the number of phlebotomies was addressed by Hutchinson et al 10 First, they showed that with a postprandial iron absorption test, non-heme iron absorption was significantly reduced when taking PPIs.…”
mentioning
confidence: 97%
“…The first prospective randomized trial in hereditary hemochromatosis to achieve the target serum ferritin level Յ50 g/L showed that erythrocytapheresis is highly effective in reducing iron overload and lowering the total number of procedures by at least 50% compared with phlebotomy, and it also shortens treatment duration. 4 For the third indication, RCE is performed to remove abnormal RBCs and replace them with donor RBCs.…”
Section: Introductionmentioning
confidence: 99%